2020
DOI: 10.21640/ns.v12i25.2618
|View full text |Cite
|
Sign up to set email alerts
|

Selectividad de insecticidas con el parasitoide Tamarixia triozae (Hymenoptera: Eulophidae) para el control de Bactericera cockerelli (Hemiptera: Triozidae)

Abstract: Introducción: Bactericera cockerelli es un insecto que daña cultivos de solanáceas, principalmente papa (Solanum tuberosum L) y tomate (Solanum lycopersicum L). El manejo de B. cockerelli ha sido el control químico; sin embargo, se han tratado de implementar otras estrategias de control con insecticidas menos tóxicos para el medio ambiente, la salud humana e insectos no blanco. Esta implementación consiste en incluir organismos de control biológico como depredadores, parasitoides, insecticidas de origen natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…When nymphs developed to the 5th instar on the 1st infested plant, we harvested all nymphs on the infested plants using a paintbrush to obtain insects of all instars at the same time. We identified and separated nymph instars under a stereomicroscope (Leica MZ12, Germany), according to Vega-Chávez (2010) . We then transferred harvested nymphs into Petri dishes according to experimental design.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When nymphs developed to the 5th instar on the 1st infested plant, we harvested all nymphs on the infested plants using a paintbrush to obtain insects of all instars at the same time. We identified and separated nymph instars under a stereomicroscope (Leica MZ12, Germany), according to Vega-Chávez (2010) . We then transferred harvested nymphs into Petri dishes according to experimental design.…”
Section: Methodsmentioning
confidence: 99%
“…Several authors have observed feeding and oviposition behaviors of T. triozae on TPP. For example, Vega-Chávez (2010) has given brief qualitative descriptions of host feeding actions and host responses. In a nonchoice setting, Caudillo Ruiz (2010) has provided a brief note of oviposition behavior on the 4th-instar nymphs and nymph responses to attacks.…”
Section: Introductionmentioning
confidence: 99%